2021
DOI: 10.1063/5.0049270
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale continuous quantum light sources based on driven dipole emitter arrays

Abstract: Regular arrays of two-level emitters at distances smaller than that of the transition wavelength collectively scatter, absorb, and emit photons. The strong inter-particle dipole coupling creates large energy shifts of the collective delocalized excitations, which generates a highly nonlinear response at the single and few photon level. This should allow us to implement nanoscale non-classical light sources via weak coherent illumination. At the generic tailored examples of regular chains or polygons, we show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…We have demonstrated that geometry can be used to alter the collective optical properties of the array and shape the temporal profile and statistics of the emitted light. This presents the opportunity to use atomic arrays to produce directional single photons 58 , correlated photons 13 , or superradiant lasers 59 . Alternatively, measurement of the emitted light provides a window into the complex evolution of the atomic system, and directional detection may enable heralded production of many-body entangled dark states.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that geometry can be used to alter the collective optical properties of the array and shape the temporal profile and statistics of the emitted light. This presents the opportunity to use atomic arrays to produce directional single photons 58 , correlated photons 13 , or superradiant lasers 59 . Alternatively, measurement of the emitted light provides a window into the complex evolution of the atomic system, and directional detection may enable heralded production of many-body entangled dark states.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, atoms trapped in a periodic subwavelength planar optical lattice have been shown in experiments to exhibit collective, spatially delocalized subradiant optical excitations [12], and related experiments on collective excitations have also been performed in other periodic structures [13,14]. Cooperatively responding optical systems of subwavelength atomic arrays have inspired a large body of theoretical studies, with examples including manipulation of subradiance [15][16][17][18], single-photon storage [19][20][21], atom and excitation statistics [22,23], optical cavity-like phenomena [24][25][26], collective antibunching [27][28][29], connected arrays [30], optomechanics [31], and parity-time symmetry breaking [32]. In particular, it was recently shown how a bilayer array of atoms could form a Huygens' surface via emerging collective excitations that mimic an array of crossed electric and magnetic dipoles, even when the atoms only undergo electric dipole transitions [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Subradiant states in free-space 2D arrays of atoms [1-3, 6, 8, 10, 11, 16, 18, 24, 32, 46-48] are promising for light storage due to their isolation from the environment, but, unlike in the case of 1D chains of atoms [49,50], in 2D arrays strongly subradiant modes cannot be directly driven by incident fields. Previous proposals have demonstrated how such modes can be excited in the steady state, using atomic level shifts to control the orientation of the dipoles [3,31], or by optimizing driving [51].…”
Section: Introductionmentioning
confidence: 99%